Pengaruh Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan: Studi pada Karyawan Generasi Z PT. Desa Wisata Indonesia di Objek wisata Dusun Semilir Kabupaten Semarang - Riestiana Purwaji Putri; Riyono Riyono; Hesti Ristanto (International Forum of Researchers and Lecturers, 2026)
This study aims to determine and analyze: 1) the effect of workload on the performance of Generation Z employees at PT. Desa Wisata Indonesia in the Dusun Semilir tourist attraction, Semarang Regency; 2) the effect of work motivation on the performance of Generation Z employees at PT. Desa Wisata Indonesia in the Dusun Semilir tourist attraction, Semarang Regency; and 3) the simultaneous effect of workload and work motivation on employee performance. The population in this study was all 120 Generation Z employees at PT. Desa Wisata Indonesia in the Dusun Semilir unit, Semarang Regency. This study used a purposive sampling technique with a sample size of 92 respondents. Data collection was conducted through questionnaires, while data analysis used multiple linear regression with the help of SPSS. The results showed that: 1) workload had a positive and significant effect on employee performance, 2) work motivation had a positive and significant effect on employee performance, and 3) workload and work motivation simultaneously had a significant effect on the performance of Generation Z employees at PT. Desa Wisata Indonesia in the Dusun Semilir unit, Semarang Regency.